Informed consent for human genetic and genomic studies: a systematic review. (18th April 2014) - Khan, A.; Capps, B.J.; Sum, M.Y.; Kuswanto, C.N.; Sim, K.
<x xml:space="preserve">Abstract</x> As genetic and genomic studies grow in scale, there are ethical concerns related to the collection and use of genetic information. The emergence of large public databases potentially redefine the terms of participation in genetic and genomic research, and suggests the changing application of traditional ethical principles such as privacy or consent. For this study, we wanted to see whether such developments are reflected in the informed consent processes in human genetic and genomic studies. Therefore, we performed a systematic review of the empirical studies that examined informed consent involving large genetic databases in human genetic and genomic studies, grouped the identified issues related to the different stakeholders (including subjects, researchers, and institutional review boards) and discussed the limitations and implications of these findings. Major themes related to the place of bioethical considerations, procured tissues, people involved, process of informed consent and study procedures. Frequently raised issues included confidentiality of participants, documentation of informed consent, public attitudes, future use of participant samples or data, and disclosure of results. Awareness and attention to these bioethical issues as well as assiduousness in managing these concerns in genetic/genomic research would further strengthen and safeguard the rights, safety and well‐being of genetic research participants.